Comparision between European and United States fares. (Civil Aviation Authority LondonGB, 1983)
Makes a detailed comparision of UK-Europe 'normal' fares with comparable fares on US domestic routes from New York and Atlanta. Compares a sample of UK-Europe and US domestic routes over the full range of the fares on offer on each. Also extends the comparison to yields, giving a broad indication of how many people are travelling at what fare levels.
DC